Acquisition of case markers in typically developing 3-7 years old Nepali speaking children - Pokharel, Sujal; Sharma, K.; Shrestha, S. (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Objective: To describe spoken language case markers of Nepali language, to study their presence in typically developing children in the age of 3-4, 4-5, 5-6, and 6-7 years in the conversational sample and picture description and to report on the frequency of occurrence of these case markers in the obtained sample. Material and Methods: 87 (male=54, female=33) typically developing Nepali speaking children of age range 3-7 years, were randomly selected from english schools at kathmandu (Oriental Academy and Mount Secondary English Boarding School) between June 2011 to June 2012. Participants were assigned into 4 groups (i.e. 3-4 years, 4-5 years, 5-6 years and 6-7 years) according to their age during sample collection. Common case markers of Nepali were selected. Conversational samples were collected and analysed. Results There is a general increase in the acquisition as well as the frequency of usage of any type of case marker with the increase in the age of children. Among the different types of case markers, nominative and locative case marker types are the most developed type of case markers among any age group of children. Conclusion: There is an overall positive progression in the acquisition of types of case markers as well as their frequency of occurrence along with the increase in age of the child in normal typically developing children in Nepali language